Interviewer effects in measuring network size using a single name generator - Marsden, Peter V (Social networks, 2003)
Name generators used to measure egocentric networks are complex survey questions that make substantial demands on respondents and interviewers alike. They are therefore vulnerable to interviewer effects, which arise when interviewers administer questions differently in ways that affect responses-in this case, the number of names elicited. Van Tilburg [Sociol. Methods Res. 26 (1998) 300] found significant interviewer effects on network size in a study of elderly Dutch respondents; that study included an instrument with seven name generators, the complexity of which may have accentuated interviewer effects. This article examines a simpler single-generator elicitation instrument administered in the 1998 General Social Survey (GSS). Interviewer effects on network size as measured by this instrument are smaller than those found by Van Tilburg, but only modestly so. Variations in the network size of respondents within interviewer caseloads (estimated using a single-item “global” measure of network size and an independent sample of respondents) reduce but do not explain interviewer effects on the name generator measure. Interviewer differences remain significant after further controls for between-interviewer differences in the sociodemographic composition of respondent pools. Further insight into the sources of interviewer effects may be obtained via monitoring respondent–interviewer interactions for differences in how name generators are administered.